LEXICAL FEATURES OF THE VERNACULAR OF THE RUSSIAN LANGUAGE - Xodjayeva D.Sh (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is about the lexical features which are not allowed in the literary language in Russian, although they are found in this language, they are not used within the literary language